Saunders nursing drug handbook 2013 - Hodgson, Barbara B.; Kizior, Robert J. (St. Louis, Missouri : Elsevier Saunders, 2013)
Saunders Nursing Drug Handbook 2013 is designed as an easy-to-use source of current drug information to help the busy nurse meet these challenges. What separates this book from others is that it guides the nurse through patient care to better practice and better care.
Drugs by disorder -- Drug classifications -- A-Z drug entries.
Includes index.
Keywords: PHARMACEUTICAL PREPARATIONS